Pulmonary Infection Caused by Achromobacter xylosoxidans in a Patient with Carcinoma of Epiglottis: A Rare Case - Priyamvada Roy (Journal of Clinical and Diagnostic Research, 2014)
Achromobacter xylosoxidans is an aerobic, motile, oxidase and catalase positive, non-fermenting, gram negative bacillus. It is an opportunistic pathogen which is responsible for various nosocomial and community-acquired infections. However, there are only very few reports of pulmonary infections caused by this bacterium in cancer patients. We are presenting a case of a patient with carcinoma of epiglottis, who developed pulmonary infection caused by Achromobacter xylosoxidans. According to the available literature, this is the first case of pulmonary infection caused by Achromobacter xylosoxidans, which was detected in a cancer patient in India. Since Achromobacter xylosoxidans demonstrates resistance to many classes of antimicrobials, vigilant and efficient microbiological work-ups and surveillances are needed, to diagnose infections caused by this rare pathogen in clinical settings.